Productions of bottom and bottom-strange mesons in pion and kaon induced reactions - Jing Liu; Quan-Yun Guo; Qi Wu; Jun He; Dian-Yong Chen (European Physical Journal C: Particles and Fields)
Abstract In the present work, we propose to explore the productions of the bottom and bottom-strange mesons in the high-energy pion and kaon-induced reactions on a proton target. The cross sections are evaluated with an effective Lagrangian constructed by the heavy-quark limit and chiral symmetry. Our estimations show that at $$P_π =80$$ P π = 80 GeV, the cross sections for B(5279), $$B^*(5325)$$ B ∗ ( 5325 ) , $$B_0^*(5722)$$ B 0 ∗ ( 5722 ) , $$B_1^′ (5716)$$ B 1 ′ ( 5716 ) , $$B_1(5721)$$ B 1 ( 5721 ) and $$B_2^*(5747)$$ B 2 ∗ ( 5747 ) production processes are estimated to be 3.19–86.26, 1.86–51.29, 0.88–24.33, 0.86–23.69, 162.35–4477.66, and 57.16–1604.43 nb, respectively, where uncertainties arise from the model parameter. In addition, the cross sections for the corresponding bottom-strange mesons production processes are very similar. From the heavy quark effective theory point of view, the ratios between the cross sections for bottom mesons and bottom-strange mesons should be similar and the present estimations are consistent with the expectation of heavy quark limit. In particular, the cross-section ratios related to the states in the same doublets are of order one. The cross sections related to the states in the T doublets are about two orders larger than those related to the states in the S doublets.